(untitled) (Research, Society and Development, 2024)
The aim of this paper is to analyze how opinions on Brazilian educational problems are presented on the social network X. X stands out for being a rich source of opinions and discussions that raise awareness of social and educational issues. The research uses a mixed methods approach, adopting the study of discourses in social media. Data was collected by extracting Twitter comments containing the codes "problems", "education" and "Brazil" from January to December 2022. The data was analyzed using the content analysis technique and was examined in three stages: pre-analysis, exploration of the material and treatment and interpretation of the results. Confirming the existence of ideas and discussions on the subject of educational problems, identifying that these are mainly presented in 3 pillars: quality, management and valorization.